1998
DOI: 10.1177/095632029800900502
|View full text |Cite
|
Sign up to set email alerts
|

Potent β-Lactam Inhibitors of Human Cytomegalovirus Protease

Abstract: A series of novel monobactam inhibitors of human cytomegalovirus (HCMV) protease has been described that possess a heterocyclic thiomethyl side chain at C-4. Changes to the heterocycle did not significantly change the inhibitory activity of these compounds in an enzymatic assay, although improvements in solubility and cell culture activity were noted. A number of permutations between C-4 substitutions and N-1 derivatives led to the identification of several β β-lactams with antiviral activity in a plaque reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…Since yeast encodes a pleiotrophic drug resistance network with a variety of ABC transporters that efficiently clear small molecules within the cell, we sensitized the strain by deleting the three major drug efflux pumps Pdr5p, Snq2p, and Yor1p. In such a setup, the yeast system shows a sensitivity towards small molecules similar to that shown in a mammalian cellular assay, at least for the ␤-lactam inhibitors tested, with a calculated EC 50 of 31 M in the yeast assay versus 78 M in a mammalian plaque reduction assay (42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since yeast encodes a pleiotrophic drug resistance network with a variety of ABC transporters that efficiently clear small molecules within the cell, we sensitized the strain by deleting the three major drug efflux pumps Pdr5p, Snq2p, and Yor1p. In such a setup, the yeast system shows a sensitivity towards small molecules similar to that shown in a mammalian cellular assay, at least for the ␤-lactam inhibitors tested, with a calculated EC 50 of 31 M in the yeast assay versus 78 M in a mammalian plaque reduction assay (42).…”
Section: Discussionmentioning
confidence: 99%
“…In order to assess sensitivity of the selection system towards small molecules, the two validated HCMV protease inhibitors BI31 and BI36 of Boehringer Ingelheim were applied (42) Figure 5A shows that increasing concentrations of both BI31 and BI36 in cells expressing the active protease correlate with increasing cell proliferation. The calculated EC 50 of 31 M for BI36 suggests that the yeast-based assay exhibits the same sensitivity as that of a mammalian cellular assay, at least for this class of compounds (42). At BI36 concentrations of Ͼ100 M, HCMV protease was strongly inhibited, as evidenced by proliferation rates similar to those of cells expressing the inactive protease.…”
Section: Modulation Of Hcmv Protease Expression Level Correlates Withmentioning
confidence: 99%
“…These compounds inhibit HCMV protease via the opening of the β-lactam ring followed by acyl enzyme complex formation. Among them, N-methylthiotetrazole-containing compounds were found to be most potent inhibitors in enzymatic assays [115]. Subsequently, Ogilvie et al reported only modest antiviral activity of monobactam inhibitors, despite the fact that many compounds were very effective in enzymatic assays [116].…”
Section: H Current Activity In Drug Discoverymentioning
confidence: 98%
“…The penicillin with the β-lactam ring has been reported earlier as antiviral protease inhibitors 48,49 , but they were not explored further as better antiviral agents were existing. Also, like N3 inhibitor, there were several molecules reported being covalent inhibitors of M pro for SARS-CoV and MERS-CoV.…”
Section: Covalent Dockingmentioning
confidence: 99%